2017
DOI: 10.1044/2016_jslhr-s-16-0218
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intelligibility Gains in Individuals With Dysarthria From Baseline Speech Features

Abstract: Assessments of baseline speech features can be used to predict appropriate treatment strategies for speakers with dysarthria. Further development of these assessments could provide the basis for more individualized treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 46 publications
(99 reference statements)
0
22
0
Order By: Relevance
“…Our recent work has demonstrated that the presence of certain speech characteristics at a baseline assessment can predict degree of intelligibility gain when a person with dysarthria is cued to speak louder or reduce their speech rate. 38 However, it is unclear whether these speech features can further distinguish variation in intelligibility gains among speakers with the same dysarthria subtype and etiology. Indeed, this question is particularly pertinent in the case of hypokinetic dysarthria, as this subtype is frequently targeted in speech therapy focused on behavioral speech modification.…”
Section: A Multivariate Analysis Of Factors Affecting Intelligibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent work has demonstrated that the presence of certain speech characteristics at a baseline assessment can predict degree of intelligibility gain when a person with dysarthria is cued to speak louder or reduce their speech rate. 38 However, it is unclear whether these speech features can further distinguish variation in intelligibility gains among speakers with the same dysarthria subtype and etiology. Indeed, this question is particularly pertinent in the case of hypokinetic dysarthria, as this subtype is frequently targeted in speech therapy focused on behavioral speech modification.…”
Section: A Multivariate Analysis Of Factors Affecting Intelligibilitymentioning
confidence: 99%
“…To examine this further, we present a new data analysis of the 23 participants with hypokinetic dysarthria (see Fletcher and colleagues for a full description of the participants 38 ). The aim is to demonstrate whether specific speech features can predict the types of speakers who will be most amenable to various cues to modify their speech-in this case, cues to speak louder and slow speech rate.…”
Section: A Multivariate Analysis Of Factors Affecting Intelligibilitymentioning
confidence: 99%
See 3 more Smart Citations